Comprehensive Urinomic Identification of Protein Alternatives to Creatinine Normalization for Diagnostic Assessment of Lupus Nephritis - Soomro, Sanam; Stanley, Samantha; Lei, Rongwei; Saxena, Ramesh; Petri, Michelle; Mohan, Chandra (Frontiers in Immunology, 2022)
Introduction: The current gold standard used for urine biomarker normalization, creatinine, poses a challenge to translate to the point of care because antibodies to creatinine are difficult to develop and currently available ligands to creatinine are sub-optimal for this purpose. Hence, protein alternatives to creatinine are clearly needed. To address this need, lupus nephritis was selected as a model disease where urine protein assessment is required for diagnosis. Methods: A comprehensive proteomic screen of 1129 proteins in healthy and lupus nephritis urine was executed to identify protein alternatives to creatinine for the normalization of urine biomarkers. Urinary proteins that correlated well with creatinine but did not vary with disease were further validated by ELISA in an independent cohort of lupus nephritis subjects. Results: The comprehensive proteomic screen identified 14 urine proteins that correlated significantly with urine creatinine but did not differ significantly between SLE and controls. Of the top five proteins selected for ELISA validation, urine HVEM and RELT once again showed significant correlation with urine creatinine in independent cohorts. Normalizing a lupus nephritis biomarker candidate ALCAM using urinary HVEM demonstrated comparable diagnostic ability to creatinine normalization when distinguishing active lupus nephritis from inactive SLE patients. Conclusions: The discovery of urine HVEM as a protein alternative to creatinine for biomarker normalization has applications in the engineering of antibody-based point of care diagnostics for monitoring lupus nephritis progression.